Performance of Protective Clothing 1986
DOI: 10.1520/stp17310s
|View full text |Cite
|
Sign up to set email alerts
|

Fabric Parameters and Pesticide Characteristics That Impact on Dermal Exposure of Applicators

Abstract: Fabric functional finish and formulation of pesticides are factors that contribute to pesticide wicking, wetting, and penetration. Fluorocarbon soil-repellent finishes inhibit contamination of the fabric and of sentinel pads. An undergarment layer offers better protection than does a single layer. Spun-bonded olefin offers protection of the same magnitude as soil-repellent finishes. Methyl parathion residues after laundering were similar for the unfinished fabric, the durable-press finished fabric, and the soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…While an insignificant difference was found in washing temperatures for the removal of methyl parathion, removal was slightly greater at the higher temperature (Laughlin, Easley, Gold, & Hill, 1986;Laughlin & Gold, 1989b). An increase in water temperature resulted in an increase in pesticide removal for Guthion and Captan (Easter, 1983) .…”
Section: Clothing Worn Bv Pesticide Workersmentioning
confidence: 88%
“…While an insignificant difference was found in washing temperatures for the removal of methyl parathion, removal was slightly greater at the higher temperature (Laughlin, Easley, Gold, & Hill, 1986;Laughlin & Gold, 1989b). An increase in water temperature resulted in an increase in pesticide removal for Guthion and Captan (Easter, 1983) .…”
Section: Clothing Worn Bv Pesticide Workersmentioning
confidence: 88%
“…Laughlin et al (1986) pipetted 0.2 mL of diluted methyl parathion onto Tyvek~ and a total of 0.2 °6 penetrated to a 50 cotton/50 polyester poplin underlayer and a collector pad. Two studies used a contamination procedure similar to the pipetting procedure used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently the use of disposable, nonwoven coveralls for pesticide applicators has gained some attention (Branson, DeJonge, & Munson, 1986;Hobbs & Oakland, 1988;Laughlin, Easley, Gold, & Hill, 1986;Leonas, 1986;Lloyd, Bell, Howarth, & Samuels, 1985;Orlando, Branson, Ayers, & Leavitt, 1981;Perkins, 1988;Staiff, Davis, & Stevens, 1982). Recently the use of disposable, nonwoven coveralls for pesticide applicators has gained some attention (Branson, DeJonge, & Munson, 1986;Hobbs & Oakland, 1988;Laughlin, Easley, Gold, & Hill, 1986;Leonas, 1986;Lloyd, Bell, Howarth, & Samuels, 1985;Orlando, Branson, Ayers, & Leavitt, 1981;Perkins, 1988;Staiff, Davis, & Stevens, 1982).…”
mentioning
confidence: 99%
“…Little research was identified that documents the result of exposure of textile or glove materials to granular pesticides. Laughlin et al (1986) compared fabric contamination with emulsifiable concentrate, wettable powder, and encapsulated methyl parathion; they found less contamination from the encapsulated product, based on a method that converted the granules to dilute solution for use in contamination. Bratten (1988) studied transfer of aldecarb from Timek ® granular pesticides to fabric, focusing on the effect of sebum soiling and perspiration.…”
mentioning
confidence: 99%